Drug poisoning: a study over secondary data in Brazil (Research, Society and Development, 2020)
Medicines have an indispensable duty when it comes to reducing the population mortality and morbidity rates, but even with the growth of therapeutic resources to fight diseases, there is also an increase in the number of occurrences related to drug poisoning. To evaluate the percentages of drug poisoning in Brazil during the 2013 to 2017 years. The details collected for the research were obtained in the secondary data related to human drug poisoning records, available from the National Toxic-Pharmacological Information System (SINITOX). It was observed that the drugs had prominent positions in poisoning compared to other toxic agents. There was a predominance of females (62.79%) over males (36.75%) and children from 1 to 4 years old (28.41%) were the most susceptible to poisoning, as well as suicide attempt (37.75%) stood out as the main circumstance in the outcome of drug poisoning. Most cases of human drug poisoning evolved to cure (51.98%). The analysis of reported cases of drug poisoning contributed as a warning, it is necessary to create actions such as the expansion of pharmaceutical care services and the improvement of public health policies in order to reverse the current situation of poisoning caused by the use of drugs.